2013
DOI: 10.1039/c2cp41894k
|View full text |Cite
|
Sign up to set email alerts
|

Exploring a charge-central strategy in the solution of Poisson's equation for biomolecular applications

Abstract: Continuum solvent treatments based on the Poisson–Boltzmann equation have been widely accepted for energetic analysis of biomolecular systems. In these approaches, the molecular solute is treated as a low dielectric region and the solvent is treated as a high dielectric continuum. The existence of a sharp dielectric jump at the solute–solvent interface poses a challenge to model the solvation energetics accurately with such a simple mathematical model. In this study, we explored and evaluated a strategy based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(43 citation statements)
references
References 78 publications
2
41
0
Order By: Relevance
“…T phase transition anomalies (T M-T ) based on Refs. [22,23], and [35]. Only one sharp peak at 218°C can be observed in sample 12#, which confirms that this crystal sample is T phase at room temperature.…”
Section: Temperature-induced Dielectric Anomalies and Phase Evolutionsupporting
confidence: 86%
See 2 more Smart Citations
“…T phase transition anomalies (T M-T ) based on Refs. [22,23], and [35]. Only one sharp peak at 218°C can be observed in sample 12#, which confirms that this crystal sample is T phase at room temperature.…”
Section: Temperature-induced Dielectric Anomalies and Phase Evolutionsupporting
confidence: 86%
“…M A ? T as reported in previous studies [22,23,44]. High value of S m for crystal sample 9# was achieved (*0.95 % at room temperature), and then dropped to *0.8 % at 90°C at which the crystal is in M A phase and the phenomenon of bifurcated S-E curve disappears.…”
Section: Electrical Characterizations and Temperatureproperty Relatiomentioning
confidence: 54%
See 1 more Smart Citation
“…To further improve the performance of the device, great efforts have been devoted to optimizing ruthenium dyes to match with cobalt mediators [19e23]. By using octadecylphosphonic acid as a co-adsorbent, Liu et al reported a PCE of up to 8.5% for DSSC employing Z907 and [Co(bpy) 3 ] 2þ/3þ [24]. Moreover, a PCE of 8.6% was achieved by tuning the highest occupied molecular orbital (HOMO) of dye and introducing the alkoxy substituents to insulate the TiO 2 surface [25].…”
Section: Introductionmentioning
confidence: 99%
“…1 Due to the high dimensionalities of typical biomolecular systems, it is extremely important to increase the accuracy and efficiency of PBE models. 2 …”
Section: Introductionmentioning
confidence: 99%